2023
DOI: 10.1021/acsomega.2c06949
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: An Emerging Target for Developing Effective Analgesics

Abstract: Inadequate treatment of acute and chronic pain causes depression, anxiety, sleep disturbances, and increased mortality. Abuse and overdose of opioids and the side effects associated with chronic use of NSAID illustrate the need for development of safer and effective pain medication. Working toward this end, an in silico tool based on an emergent intelligence analytical platform that examines interactions between protein networks was used to identify molecular mechanisms involved in regulating the body's respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Traditional medicines including vitamins, vegetable/animal oils, and treatments obtained from plants and animals have been used as therapeutic agents for the treatment of psoriasis (Raut & Wairkar, 2018). Our previous study, we evaluated the efficacy of krill oil, cannabidiol, and myo-inositol to alleviate formalin-induced inflammatory pain, and found that the combinations of cannabidiol and myo-inositol potentiated the efficacy of krill oil (Manivasakam et al, 2023). This study also evaluated the antipsoriatic effects of krill oil-containing combinations using an IMQ-induced psoriasis mice model and found strong evidence supporting their use as an antipsoriatic agent.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional medicines including vitamins, vegetable/animal oils, and treatments obtained from plants and animals have been used as therapeutic agents for the treatment of psoriasis (Raut & Wairkar, 2018). Our previous study, we evaluated the efficacy of krill oil, cannabidiol, and myo-inositol to alleviate formalin-induced inflammatory pain, and found that the combinations of cannabidiol and myo-inositol potentiated the efficacy of krill oil (Manivasakam et al, 2023). This study also evaluated the antipsoriatic effects of krill oil-containing combinations using an IMQ-induced psoriasis mice model and found strong evidence supporting their use as an antipsoriatic agent.…”
Section: Resultsmentioning
confidence: 99%
“…67,71,72,[121][122][123][124] Recent animal-based and in silico experiments suggest the regulation of autophagy plays a central role in the modulation of pain symptoms. 12 That role is mainly supported by the anti-inflammatory action of autophagy. Mechanistically, BDNF, P2X4R, and P2X7R are linked by ATP as it activates both receptors and mediates the release of BDNF from microglia in migraine.…”
Section: Con Cluding Remark S and Per S Pec Tive Smentioning
confidence: 99%
“…Functionally, this association may be underlined by several effects, but neuroinflammation is the most consistently reported link 67,71,72,121–124 . Recent animal‐based and in silico experiments suggest the regulation of autophagy plays a central role in the modulation of pain symptoms 12 . That role is mainly supported by the anti‐inflammatory action of autophagy.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations